From ashes to understanding: Opinion papers on fire and a call for papers for a Special Issue in Flora - Overbeck, Gerhard E.; Silveira, Fernando A. O.; Rossatto, Davi R. [UNESP]; Heilmeier, Hermann (Elsevier B.V., 2020)
In the recent past, wildfires have received much attention both by science and by the media, especially in relation to deforestation, degradation and climate change and when affecting fire-sensitive ecosystems. On the other hand, fire is a natural process in many ecosystems, in particular those to be considered fire-dependent; here, maintaining natural fire regimes is important to maintain biodiversity and ecosystem services. In many regions of the world we are still in the need for a better understanding of fire effects on plant populations, communities and ecosystems. For instance, responses of individuals and populations to heat and fire can differ among distinct fire-prone ecosystems, and community level responses often vary depending on historical disturbance regimes or the fire regime as such. Effects on ecosystem processes, e.g. on carbon cycles, can vary greatly in scale and are even more difficult to predict. This adds up to uncertainties regarding appropriate fire management strategies, both in fire-prone and fire-sensitive ecosystems. Here, we introduce a set of opinion papers on fires in Brazil and a forthcoming Virtual Special Issue of Flora - Morphology, Distribution, Functional Ecology of Plants on Fire and vegetation, with contributions expected from a broad range of topics related to fire, plants, and vegetation. This special issue will contribute to the development not only of more knowledge on fire effects on plants and vegetation, but also to advances in fire management policies in different ecosystems around the world. The main issue, after all, is to go beyond simple classification of fires as 'good' or 'bad', but rather to develop strategies to deal with changing fire regimes and their effects in a dynamic world increasingly modified by human actions.
Keywords: Wildfire; Disturbance; Fire-prone; Fire-sensitive; Vegetation fire; Fire management